Conservation and sustainable use of biodiversity of fruit crops and wild fruit species. Proceedings of International scientific and practical conference, 23-26 August 2011, Tashkent, Uzbekistan - Turdieva, M.K.; Kayimov, A.K.; Baymetov, K.I.; Mustafina, F.U.; Butkov, E.A. (Bioversity International, 2012)
More than 80 scientists and development officers from Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, Uzbekistan, Armenia, Azerbaijan, Georgia, China, Czech viii Republic, Sri Lanka and Bioversity International exchanged results of their research and development projects on agrobiodiversity management, including policy issues, methodologies on assessment of agrobiodiversity distribution and diversity level, actions on increasing public awareness on value and importance of plant genetic resources, establishment of partnership and strengthening collaboration, building capacity of stakeholders to perform successfully their roles in plant diversity maintenance.